A Natural Semantic Language Approach to Dawan Verb ‘To Take’ - Maria Gaudensiana Sona; I Wayan Budiarta (RETORIKA: Jurnal Ilmu Bahasa, 2018)
This research investigates the study of Natural Semantic Metalanguage (NSM) to the verb mait 'to take' of Dawan - East Nusa Tenggara Province, Indonesia. Typically the study describes the semantic structure and the semantic role of the argument of the mait. I made use of Goddard’s theory of NSM (Goddard, 1997) in dealing with the verb analysis. Data were obtained from 5 Dawan native informants. Results of data analysis show that the verb of Dawan has a significant meaning in line with the concept of semantic of the verb mait "to take", oet "to cut", usik "to despoil", main " to pick up", kui "to waste", heut "to pick", so "to spoon", abakat "to rob", nakolo "to pilfer", mpoel "to throw", mbok "to pull", Nak Haen "dig", Muhabi "pinning", Huk "catch", and Iup "broken". The semantic structure based on the argument that fills the verb is if one "takes", the component mapping is "X does something on Y" and therefore this "Y moves through X" at the same time; X wants this; X does something like this.